Learning Strategies at SD Muhammadiyah Balongbendo 10 during the covid 19 pandemic - Muhlasin Amrullah; Elsah Isnaini (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to find out the strategies applied at SD Muhammadiyah 10 Balongbendo in learning during the covid 19 pandemic. This scientific work examines various aspects, including the history, strategies, challenges and facilities contained in SD Muhammadiyah 10 Balongbendo. The learning strategy that can be reached in the world of education is online learning. Online learning is carried out remotely, but equipped with various types of applications that support it. The purpose of the study was to obtain an overview of the implementation of learning during the Covid-19 pandemic along with the strategies implemented at SD Muhammadiyah 10 Balongbendo as an effort to monitor and identify learning that is currently running even though the situation has not been able to support it optimally. The subjects of this study were students of SD Muhammadiyah 10 Balongbendo who carried out an online learning program. This research is a descriptive qualitative research. Data were collected by direct interviews which took place in the principal's office of SD Muhammadiyah 10 Balongbendo. The results of this study are (1) the form of strategies carried out during the pandemic, (2) online learning that continues to run (3) Cooperation between educators and parents in the distance learning process. The conclusion in this study is that the teacher's learning strategy has been implemented using several kinds of learning media that have been applied to realize the appropriate learning objectives.